PEMANFAATAN BANGUNAN CAGAR BUDAYA BENTENG KEDUNG COWEK SEBAGAI PARIWISATA SEJARAH - Agus Nur Rochman Suwargi; Dian Hariyanti; Siti Raisha Della Vega; Dinar Rizky Listyaputri (KRONIK : Journal of History Education and Historiography, 2023)
The long history experienced by the Indonesian nation and various events ranging from the formation of the Kingdom to the Reformation have made historic buildings or relics found in almost all regions and cities in Indonesia. The city of Surabaya is one of the cities that has many well-known historical sites. The Surabaya City Government has made efforts to revitalize and improve various kinds of historical sites so they can become tourist attractions and cultural heritage sites. This aims to align the image of the city of Surabaya with the title “City of Heroes.” Even so, there are still historical buildings that are not maintained and seem abandoned, one of which is Fort Kedung Cowek. This fort, which is a legacy of the Dutch East Indies Government, has existed since 1900 and is also related to the 11 November Incident in Surabaya. Therefore, with this background and relatively high welfare values, the research aims to find the potential for the proper utilization of Fort Kedung Cowek as historical tourism in the city of Surabaya. The methods used in this research are the historical method and the descriptive qualitative method to obtain results or conclusions from the theme taken, namely the potential use of Fort Kedung Cowek as historical tourism.